Indonesian Language Teaching Model for Foreign Speakers Cross Generations - Suharsono, Degita Danur; Kamal, Mushthofa; Wicaksono, Julien Arief; Widianto, Eko (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2024)
Perkembangan teknologi dan komunikasi telah melahirkan generasi Baby Boomers, generasi X, generasi Y, generasi Z, dan generasi Alfa. Setiap generasi memiliki karakteristik yang berbeda dalam kegiatan pengajaran. Pengajaran bahasa Indonesia bagi penutur asing (BIPA) dapat diikuti mulai dari generasi Baby Boomers hingga generasi Alfa. Perbedaan karakteristik antargenerasi dalam pengajaran BIPA perlu dilakukan penyesuaian terkait model pengajaran yang digunakan. Model pengajaran yang sesuai dengan karakteristik generasi memudahkan pelajar dan pengajar BIPA dalam mencapai tujuan pengajaran. Penelitian ini bertujuan untuk mendeskripsikan model pengajaran BIPA yang sesuai dengan karakteristik masing-masing generasi pelajar. Metode penelitian yang digunakan adalah studi pustaka. Hasil penelitian ini adalah model pengajaran BIPA lintas generasi yang terdiri dari (1) struktur pengajaran BIPA, (2) lingkungan belajar, dan (3) sistem pendukung pengajaran. Struktur pengajaran BIPA merupakan fase-fase pengajaran yang dikembangkan oleh pengajar BIPA sesuai dengan karakteristik generasi pelajar BIPA dengan tujuan mencapai standar kompetensi lulusan. Lingkungan belajar diformat berdasarkan sistem sosial dan karakteristik generasi pelajar BIPA. Sistem pendukung model pengajaran BIPA lintas generasi terdiri dari sumber belajar, media pengajaran, dan bahan ajar yang disesuaikan dengan karakteristik generasi pelajar BIPA.The development of technology and communication has been raising to the Baby Boomers generation, generation X, generation Y, generation Z, and generation Alpha. Each generation has different characteristics in learning activities. Indonesian for Speakers of Other Languages (BIPA) can be learned from the Baby Boomers generation to the Alpha generation. Characteristic differences among generations in learning BIPA should be adjusted regarding the learning model used. The suitable learning model for each generation’s characteristic makes the learning BIPA easier for the students and teachers to achieve the learning goals. This study aims to describe the BIPA learning model based on the characteristics from each generation of students. The research method used is literature studies. The results of this study are producing BIPA learning model across generation which is consisting of (1) BIPA learning procedure, (2) learning environment, and (3) learning support system. The BIPA learning procedure is the teaching phases developed by BIPA teachers based on the characteristics of the BIPA student’s generation with the purpose of achieving the competency standards. The learning environment is created based on the social system and the characteristics of the BIPA students’ generation. The support system for the across generations BIPA learning model consists of learning resources, learning media, and teaching materials that are adjusted to the characteristics of the generation of BIPA students.